Numerical Survey of Contaminant Transport and Self-Cleansing of Water in Nador Lagoon, Morocco. (27th May 2014) - Chaabelasri, E. M.; Amahmouj, A.; Jeyar, M.; Borthwick, A. G. L.; Salhi, N.; Elmahi, I.
Abstract : Numerical simulations are presented of the flow hydrodynamics and hypothetical contaminant dispersion patterns in Nador Lagoon, a shallow lagoon with a barrier island situated on the coast of Morocco. It is found that the natural circulation forced by the tidal flow in the lagoon is greatly affected by the development of an artificial inlet in the barrier island. The case study demonstrates the potential use of modern computational hydraulics as a tool integrated in the decision support system designed to manage a lagoon ecosystem.